Pengaruh Disiplin Kerja, Gaya Kepemimpinan, dan Motivasi Kerja Terhadap Kinerja Karyawan Pada Hotel Matahari Terbit Bali, Tanjung Benoa-Nusa Dua - Putra, Gede Prawira Utama (E-Jurnal Manajemen, 2013)
This research were done, in order to determined the effect of the work discipline, leadership styles, and work motivation to the employee performance either simultant or partial, to determine the most dominant variable that influenced the employee performance in Hotel Matahari Terbit Bali. The technique that used is factor analysis and multiple regression analysis. The result of the analysis showed that the variables of the work discipline, leadership styles, and work motivation has a significant communication simultan and also partial on the employee performance. The leadership styles variable, became the most dominant variable that affected the employee performance because based on the analysis calculation the Standardized Coefficients Beta has the greatest value. Keywords : work discipline, leadership styles, and work motivation